GE_GERICHTE C/1______/2015 vom 22. April 2016 - GE Cour de justice (2016)
CONDITION DE RECEVABILITÉ; INTÉRÊT DIGNE DE PROTECTION; COMPENSATION DE CRÉANCES; OBLIGATION D'ENTRETIEN | LP.278.3; CO.125.2; LP.93